2011
DOI: 10.4067/s0718-381x2011000200012
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glycemic Indexes, Hyposalivation, and Xerostomia Type 1 Diabetic Patients

Abstract: ABSTRACT:The aim of this study was to assess the relationship between glycemic control of type 1 diabetic (DM1) patients and hyposalivation and xerostomia. This observational transversal study used a quantitative approach with a sample of 25 DM1 patients enrolled at the Diabetes Association of Joinville (ADIJO) in 2008. Variables assessed were sialometry through stimulated salivary flow, complaints of xerostomia, and testing for glycemic control: fasting capillary glycemia (FCG) and glycated hemoglobin (HbA1c)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Using a disposable 5 millimeter syringe, the volume was quantified and divided by 5 (collection time) to obtain the flow in ml/min. Values of ≥0.1 ml/min at rest and ≥0.7 ml/min for stimulated saliva were considered for hyposalivation [4,9,22,24]. The values were recorded in their respective questionnaires.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using a disposable 5 millimeter syringe, the volume was quantified and divided by 5 (collection time) to obtain the flow in ml/min. Values of ≥0.1 ml/min at rest and ≥0.7 ml/min for stimulated saliva were considered for hyposalivation [4,9,22,24]. The values were recorded in their respective questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Carda et al [7] reported the presence of 76%, of which 84.21% are uncontrolled diabetics. Xerostomia can be a result of decreased salivary flow, especially the parotid gland, or even in normal salivary flow conditions [4,9,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations